HIV care cost in England: a cross‐sectional analysis of antiretroviral treatment and the impact of generic introduction. Issue 6 (29th April 2019) - Ong, KJ; van Hoek, AJ; Harris, RJ; Figueroa, J; Waters, L; Chau, C; Croxford, S; Kirwan, P; Brown, A; Postma, MJ; Gill, ON; Delpech, V
Abstract : Objectives: Reliable and timely HIV care cost estimates are important for policy option appraisals of HIV treatment and prevention strategies. As HIV clinical management and outcomes have changed, we aimed to update profiles of antiretroviral (ARV) usage pattern, patent/market exclusivity details and management costs in adults (≥ 18 years old) accessing HIV specialist care in England. Methods: The data reported quarterly to the HIV and AIDS Reporting System in England was used to identify ARV usage pattern, and were combined with British National Formulary (BNF) prices, non‐ARV care costs and patent/market exclusivity information to generate average survival‐adjusted lifetime care costs. The cumulative budget impact from 2018 to the year in which all current ARVs were expected to lose market exclusivity was calculated for a hypothetical 85 000 (± 5000) person cohort, which provided an illustration of potential financial savings afforded by bioequivalent generic switches. Price scenarios explored BNF70 (September 2015) prices and generics at 10/20/30/50% of proprietary prices. The analyses took National Health Service (NHS) England's perspective (as the payer), and results are presented in 2016/2017 British pounds. Results: By 2033, most currently available ARVs would lose market exclusivity; that is, generics could be available. Average per person lifetime HIV cost was ~£200 000 (3.5% annual discount) or ~£400 000 (undiscounted), reducing to ~£70 000 (3.5% annual discount; ~£120 000 undiscounted) with the use of generics (assuming that generics cost 10% of proprietary prices). The cumulative budget to cover 85 000 (± 5000) persons for 16 years (2018–2033) was £10.5 (± 0.6) billion, reducing to £3.6 (± 0.2) billion with the use of generics. Conclusions: HIV management costs are high but financial efficiency could be improved by optimizing generic use for treatment and prevention to mitigate the high cost of lifelong HIV treatment. Earlier implementation of generics as they become available offers the potential to maximize the scale of the financial savings.